Bioprinting: Inkjet–Spray Hybrid Printing for 3D Freeform Fabrication of Multilayered Hydrogel Structures (Adv. Healthcare Mater. 14/2018). Issue 14 (25th July 2018) - Yoon, Sejeong; Park, Ju An; Lee, Hwa‐Rim; Yoon, Woong Hee; Hwang, Dong Soo; Jung, Sungjune
Abstract : In article1800050, Sungjune Jung and co‐workers present a new bioprinting process by combining drop‐on‐demand inkjet printing with a spray‐coating technique. Successfully fabricated hydrogel structures with various shapes, sizes and materials, including alginate, cellulose nanofiber, fibrinogen, and gelatine methacryloyl‐based bioinks that are inkjet‐printable are presented. The proposed printing technique and the bioinks can be used to produce large‐scale, 3D laminated structures that potentially include the functions of native tissues such as skin and epithelium.